2019
DOI: 10.5487/tr.2019.35.1.037
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Binding Affinities of Synthetic Cannabinoids Determined by Non-Isotopic Receptor Binding Assay

Abstract: A major predictor of the efficacy of natural or synthetic cannabinoids is their binding affinity to the cannabinoid type I receptor (CB1) in the central nervous system, as the main psychological effects of cannabinoids are achieved via binding to this receptor. Conventionally, receptor binding assays have been performed using isotopes, which are inconvenient owing to the effects of radioactivity. In the present study, the binding affinities of five cannabinoids for purified CB1 were measured using a surface pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Employing an in vitro receptor-binding assay, we previously reported that JWH-210 binds to CB1 [ 33 ]. However, to the best of our knowledge, there are no studies showing the interaction of JWH-210 and CB1 in vivo [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Employing an in vitro receptor-binding assay, we previously reported that JWH-210 binds to CB1 [ 33 ]. However, to the best of our knowledge, there are no studies showing the interaction of JWH-210 and CB1 in vivo [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the last decades, there is a growing trend to replace radioligand-based techniques with more costeffective and environmentally sustainable alternative procedures for the study of different aspects of G protein-coupled receptors (GPCR), including the cannabinoid CB 1 receptor [41]. Thus, immunohistochemistry has largely displaced autoradiography for the study of CB 1 receptor distribution in histological sections [42][43][44], with the advantage of providing more accurate information on receptor distribution [45].…”
Section: Discussionmentioning
confidence: 99%